2020
DOI: 10.1007/s11869-020-00937-0
|View full text |Cite
|
Sign up to set email alerts
|

UK COVID-19 lockdown: 100 days of air pollution reduction?

Abstract: On the 23 March 2020, a country-wide COVID-19 lockdown was imposed on the UK. The following 100 days saw anthropogenic movements quickly halt, before slowly easing back to a “new” normality. In this short communication, we use data from official UK air-quality sensors (DEFRA AURN) and the UK Met Office stations to show how lockdown measures affected air quality in the UK. We compare the 100 days post-lockdown (23 March to 30 June 2020) with the same period from the previous 7 years. We find, as shown in numero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
57
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 32 publications
9
57
1
1
Order By: Relevance
“…However, a certain decrease in concentration levels appeared at the end of February, when the lockdown was already enforced in small municipalities in the middle of the Po Valley. Conversely, in March and April, they were always below q2 [14][15][16][17][18][19] (<30 µg m −3 ), and even below q1 [14][15][16][17][18][19] (<15 µg m −3 ) in 50% of the days, with the differences between mean values usually being in the 5−10 µg m −3 range, but occasionally as high as 12-15 µg m −3 . Maximum daily values of 2020 were practically always lower than in the past, lying in the q3 14-19 -max 14-19 range, and even within the IQR 14-19 sometimes, with values getting closer and closer to q3 14-19 , down to around 30-40 µg m −3 , in late April.…”
Section: Nomentioning
confidence: 89%
See 3 more Smart Citations
“…However, a certain decrease in concentration levels appeared at the end of February, when the lockdown was already enforced in small municipalities in the middle of the Po Valley. Conversely, in March and April, they were always below q2 [14][15][16][17][18][19] (<30 µg m −3 ), and even below q1 [14][15][16][17][18][19] (<15 µg m −3 ) in 50% of the days, with the differences between mean values usually being in the 5−10 µg m −3 range, but occasionally as high as 12-15 µg m −3 . Maximum daily values of 2020 were practically always lower than in the past, lying in the q3 14-19 -max 14-19 range, and even within the IQR 14-19 sometimes, with values getting closer and closer to q3 14-19 , down to around 30-40 µg m −3 , in late April.…”
Section: Nomentioning
confidence: 89%
“…For time pattern analyses at the monthly level, data distributions for each single calendar day were assembled, assessing the frequency of occurrence of 2020 data within corresponding concentration ranges observed in the previous six years. These ranges were defined based on the q1 14-19 , q2 [14][15][16][17][18][19] , and q3 [14][15][16][17][18][19] values, respectively representing the 1st, 2nd, and 3rd quartiles computed for the 2014-2019 daily datasets. The interquartile range IQR 14-19 (i.e., the concentration interval between the third and the first quartile, q3 14-19 -q1 [14][15][16][17][18][19] ) was also used for the assessment.…”
Section: Air Quality Data Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparing the air quality index of the unblocked cities and the blocked cities, it was found that the daily air quality index and PM 2.5 of the blocked cities dropped by 19.84 points (17%) and 14.07 μg m −3 (17%), and after the city blockade, the quantity indicators of CO, SO 2 , NO 2 , and O 3 are significantly reduced (He, Pan, & Tanaka). Compared with the concentration of nitric oxide (NO) in the past 7 years, the concentration of NO in the UK this year has decreased by approximately 61% (Higham et al 2021 ). During the COVID-19 virus epidemic, the prevention and control policies of various countries and regions reduced the concentration of air pollutants worldwide, optimized air quality indicators, and improved air quality conditions.…”
Section: Challenges and Solutionsmentioning
confidence: 99%